2020
DOI: 10.1007/s13760-020-01514-z
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic dystrophy type 1 as a major risk factor for severe COVID-19?

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is challenging health care systems worldwide. People with myotonic dystrophy type 1 (DM1) represent a high-risk population during infectious disease outbreaks, little is known about the potential impact of COVID-19 on patients with DM1. We studied the clinical course of COVID-19 in three hospitalized patients with myotonic dystrophy type 1 or Steinert's disease, between April 1, 2020-April 30-2020. All three had advanced Steinert's disease receiving non-invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…After the removal of duplicates and the screening of titles and abstracts, 63 studies were retained, of which 22 were suitable for qualitative synthesis (Figure 1). The studies published in October 2020 were conducted in the following World Health Organization regions: 10 in Europe (Italy, 7-10 UK, 11,12 Belgium, 13,14 Germany 15 and Spain 16 ) and 10 in the Americas (USA, [17][18][19][20][21][22][23] Brazil 24,25 and Canada 26 ); one in Western Pacific (Australia 27 ) and one in the African region (Morocco). 28 A detailed overview of this update is provided as Supplementary Digital Material 1: Supplementary Table I (available on Cochrane Rehabilitation website).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of duplicates and the screening of titles and abstracts, 63 studies were retained, of which 22 were suitable for qualitative synthesis (Figure 1). The studies published in October 2020 were conducted in the following World Health Organization regions: 10 in Europe (Italy, 7-10 UK, 11,12 Belgium, 13,14 Germany 15 and Spain 16 ) and 10 in the Americas (USA, [17][18][19][20][21][22][23] Brazil 24,25 and Canada 26 ); one in Western Pacific (Australia 27 ) and one in the African region (Morocco). 28 A detailed overview of this update is provided as Supplementary Digital Material 1: Supplementary Table I (available on Cochrane Rehabilitation website).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Due to the heterogeneity of studies, a meta-analysis was not appropriate, and the results were described qualitatively. Based on the OCEBM 2011 Levels of Evidence table 29 the majority of studies (N.=17; 77.3%) were level 4 (six case report, 7,11,17,19,22,28 eight case series, 9,10,13,14,16,21,24,27 three historical cohort 20,23,26 ), whereas the remaining five were level 3 (four cohort studies 8,12,15,25 and one cross-sectional 18 study). No RCT or QRCTs were found in this update (Table I).…”
Section: Evidence Level Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With interest we read the article by Dhont et al about three patients with myotonic dystrophy type 1 (MD1) who died from COVID-19 despite maximal therapy for the infection with SARS-CoV-2 [1]. It was concluded that MD1 patients are at high risk for severe COVID-19 disease with poor outcome [1]. We have the following comments and concerns.…”
mentioning
confidence: 99%
“…All three patients with MD1 received chloroquine from which it is well known that it can be myotoxic [2]. Unfortunately, the authors did not provide the exact medication the three patients were receiving in addition to chloroquine [1]. From various antibiotics, including azithromycin, it is known that they can be myotoxic [3].…”
mentioning
confidence: 99%